Socio-demographic profile of male drug abusers residing in Mumbai city, Maharashtra, India - Jumade, Prashil P.; Kasbe, Abhiram M.; Giri, Purushottam A. (International Journal Of Community Medicine And Public Health, 2017)
Background: The drug abusers problem is becoming worse in the metropolitan city like Mumbai, India. There come many migrant population from out of state and from inside the state for the search of job or for the sake of employment. These people are at most risk of becoming the drug abusers if they fail to get proper employment or get into the bad company. Drug abuse is becoming the emerging problem in the youth of India. Methods: A cross-sectional study was conducted during the period of January to December 2013 at de-addiction centre of NGO working for the drug abusers at 3 different sites in Mumbai city. Total 100 subjects were selected according to the convenient method sampling. Results: In this study, more than 50% were below the age of 40 years and 66% were Muslim followed by 31% were Hindu by religion. More than 50% were educated upto secondary level and were married and maximum subjects were living in nuclear family. About 71% subjects were living with their family. Total 99 out of 100 subjects were having addiction of brown sugar followed by 77 out of 100 subjects were having charas addiction. Conclusion: Maximum drug abusers were Muslim by religion followed by Hindu and age below 40 years and educated upto secondary level and were born in Mumbai only. Maximum subjects were married and living in nuclear family and were having addiction of brown sugar followed by charas.